Breathing in the fullness of time - Kloefkorn, William (University of Nebraska Press, 2009)
The "tell-all" memoir takes on new meaning in the work of poet William Kloefkorn, whose accounts of the moments and movements of life touch on everything that matters, the prosaic and the profound, the extraordinary in the everyday, and the familiar in the new and strange. The fourth and final installment in Kloefkorn's reflections, Breathing in the Fullness of Time, departs from the elements ruling the other volumes--water, fire, and earth--and floats its insights and observations, its memories and anecdotes on the now wild, now whispering element of air